Comparison of spatial and temporal variation of maize evapotranspiration in Mahidasht using Landsat 8 satellite images and available resources - Nasim Kamali; Bahman Farhadi Bansouleh (رویکردهای نوین در مهندسی آب و محیط زیست, 2022)
The crop evapotranspiration (ET) has spatial and temporal variations within the region due to changes in meteorological parameters, phenological stage, and farm management conditions. The main objective of the present study was to compare the trend of temporal and spatial variations of grain maize evapotranspiration in Mahidasht using satellite images with available resources (due to lack of Lysimeteric data). In this study, the daily evapotranspiration for the four maize farms in the different parts of the plain was calculated using Landsat 8 satellite images and the SEBAL algorithm on six dates during the growing period of maize in the year 2014. Since there was no field measurement of ET to verify the results of estimated ET based on the SEBAL algorithm, the final results (evapotranspiration) and intermediate results (Land surface temperature, Albedo, and NDVI) calculated by the SEBAL algorithm were compared with acceptable values in the literature. Results showed a similar trend of estimated evapotranspiration by the SEBAL algorithm and AGWAT software. The trend of increasing and decreasing land surface temperature was rational. The average of NDVI during the growth period in the studied farms was between 0.47 and 0.53 which was acceptable. Albedo with an average of 0.17-0.18 had slight variations between the selected farms. Results showed rising in land surface temperature, evapotranspiration, and NDVI to the middle of the growth period and then reducing of these parameters. The average estimated maize evapotranspiration based on the SEBAL algorithm was between 3.35 to 8.53 mm/day for the six imagery dates.